Impossible de s'en sortir seul. Fictions labyrinthiques et solitude chez Franz Kafka, Jorge Luis Borges, Mark Z. Danielewski et Stanley Kubrick - Message , Vincent (Amaltea. Revista de Mitocrítica, 2009)
This article aims to analyze the relationship between the pattern of the labyrinth and the theme of solitude in four works: The House of Asterion by Borges, The Burrow by Kafka, House of Leaves by Danielewski and Kubrick’s film The Shining. They all share the same scenario: alone in a maze, a character loses his mind and dies. Why is this narrative pattern so common in maze-like fictions? This can be accounted for in the original myth: the Minotaur, a character brought back by modernity, is defined by his solitude. In twentieth-century literature, labyrinths are essentially mental: they represent the inner complexity of the subject rather than a hostile environment. While depicting the idiosyncrasies of the characters who fail to survive in their labyrinth, I will demonstrate how maze-like fictions help us to understand the dialogic nature of the self. Those who perish in labyrinths are individuals who bring their refusal of interacting with others to a level of solipsism, and who believe they can master the world but do not acknowledge its complexity. Behind those characters whose examples are not to be followed, we can make out the portrait of the ideal reader of maze-like fictions.